Halal food analysis: ensuring food and other consumer goods to be authentically halal - Mirghani, Mohamed Elwathig Saeed (TM-Info-Media Sdn. Bhd., 2009)
Ensuring food and other consumer goods to be authentically halal is paramount for Muslims. Halal should involve approval of all ingredients and all food processing at any stage of the production - the concept of from farm to mouth. Bearing in mind that Muslim population is about 1.6 billion woridwide, many companies are looki at halal concept as a new tool for marketing.